The Assessment of Berth Occupancy Ratio (BOR) to Achieve Required Standardised Level and Optimum Throughput: A Case of Oil and Gas Terminal in Kalimantan - Raja Oloan Saut Gurning; Fauzan Fikri (Institut Teknologi Sepuluh Nopember, 2018)
In many cases of berth occupancy (BOR) level in the port can be one of the factors considering whether the services of port is busy or not. Later, the factors are evaluated including operational, technical or any other thing that makes this parameter to rise and affect the performance of the services of a port . In this study, the BOR assessment is applied by modeling the existing operation of an oil gas and terminal in Kalimantan using ARENA to fulfill fuel oil (BBM) and gas in the eastern part of Indonesia. The model considers various factors as the terminal service capacity and the input of terminal traffic such as increased cargo balance from time to time including ships and cargo traffic. To support the implementation of the terminal acceleration program, the analysis of utility usage dock and equipment loading - unloading (marine loading arms) is an essential item for giving arguments plans facility expansion due to the increasing traffic of ships and the cargo services through a strategic plan providing such as new facilities/equipments and other new managemet arrangement. As a result, the study may provide scenarios as options for the terminal operator to implement in achieving both the optimised throughput and acceptable BOR level by considering operational, technical, commercial and management strategies